Hosts as Gatekeepers for North American Gay and Bisexual Men's Private Group Sex Parties. Issue 8 (3rd July 2022) - Birch, Robert; Jollimore, Jody; Howard, Terry; Lal, Allan; Cui, Zishan; Rich, Ashleigh J.; Lachowsky, Nathan; Moore, David M.; Hogg, Robert S.; Roth, Eric Abella
ABSTRACT: Gay and bisexual men's (GBM) group sex parties are considered HIV risk environments due to their association with concurrent sexual partners, condomless anal sex, and polysubstance use. The possibility of group sex party hosts acting as gatekeepers to minimize risks has been suggested, but remains understudied. We analyzed qualitative data from 20 in-depth interviews with North American GBM who recently attended private group sex parties to determine if hosts' actions constitute harm reduction strategies. Results showed hosts acting as gatekeepers before parties by establishing and disseminating themes and rules, screening applicants, and selecting guests. During parties hosts enforced rules and rejected uninvited guests. By their actions, hosts established a more controlled environment compared to public sex-on-premises bathhouses, and facilitated boundary play, the paradoxical behavior of simultaneously desiring risk and safety, previously noted for GBM circuit parties. Results suggest initiating education programs focusing on private group sex party hosts as gatekeepers.